Educação física na medida socioeducativa de internação : um estudo sobre práticas educativas e mecanismos de resistência - Souza, Carolina Maciel (Universidade Federal de São Carlos, 2018)
Non-school physical education is instituted as a pedagogical dimension inherent in the implementation of socio-educational measures detention, to juvenile delinquence in the State of São Paulo. This non-school social practice is mandatory and must be offered for 3 hours a week to young people, with the assumption of incorporating the student into the body culture of movement. Faced with the still scarce number of productions on the subject, the CASA Foundation appropriates the knowledge produced on school physical education to anchor its practices. Some studies, such as Andrade (1997), Mata (2004) and Domingos (2014), produce discussions about non-school physical education of the CASA Foundation and reveal the strong sports content given to their guidelines, adapting their practices to the needs of the neoliberal subject. In view of this, this study has as a guiding question: how has institutional physical education been constituted in the socio-educational measure detetion in the State of São Paulo? To answer this question, the following objectives were outlined: characterizing the pedagogical proposal of the Institution physical education; identify and analyze educational practices; analyze the institutional difficulties for the implementation of non-school physical education at CASA; understand how the young people experience the educational practices in the day to day of the Institution. Therefore, we used the qualitative search in education, through participant observations and conversation with young people, and the data are recorded in field diary. The data collection occurred in the first trimester of 2017 and the collaboration of twelve young people who fulfill socio-educational measure of internment in the CASA Foundation. The organized data announce two major focuses of analysis that are articulated. First, the normative instances that operate in physical education classes when practices and discourses produce tensions between what the state norm seeks to develop in young people and the resistances that occur mediated by the internal codes of the criminal world. Second, institutional difficulties for the implementation of non-school physical education in CASA, since the structure of deprivation of liberty and the relationships established therein, limit social and educational processes, imposing challenges to the teaching performance, whose initial training does not include the preparation to act in these contexts. Also, the analyzes indicate inconsistency between the proposal of non-school physical education intended by the CASA Foundation and the pedagogical proposal existing in the Institution as a whole. It is suggested to review what structures physical education in this institution, since its pedagogical model, based on Paulo Freire, is against cultural domination, especially that produced in neoliberal times.
Keywords: Educação física; Medida socioeducativa de internação; Jovens em conflito com a lei; Práticas educativas; Physical education; Social - educacional measures detetion; Juvenile delinquence; Educacional practices; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO